Eco-Friendly Management Of Pulse Beetle - Regmi, Homan; Dhoj, Yubak (Journal of Agriculture and Environment, 2013)
An experiment on eco-friendly approach of managing pulse beetle (Callosobruchus chinensis L.) in chickpea (Cicer arietinum L) was carried out at the Institute of Agriculture and Animal Science (IAAS), Rampur, Chitwan, Nepal from April to July, 2007. The experiment consisted of fourteen treatments laid out in two factors Completely Randomized Design (CRD) with three replications. Among them, storage structure (aluminium sheet bin and jute bag with plastic lining) was considered as one factor and pesticidal materials (Xanthoxylum armatum DC fruit dust@ 30gm kg-1; Acorus calamus L. rhizome dust@ 30 gm kg-1; Cinnamom camphora balls@ 1.5 gm kg-1; Sesamum indicum L. oil@ 5 ml kg-1; Azadirachta indica A. Juss. leaf dust@30gm kg-1; malathion dust@ 1gm kg-1 and control) was as another factor. Among six pesticidal materials tested, mortality of adult bruchids was obtained significantly higher in chickpea treated by C. camphora balls (25.17) followed by A. calamus rizome dust (24.83) and Sesamum oil (24.50). Grain damage and weight loss was nil in chickpea treated by these three materials. Among botanicals used, X. armatum fruit dust and A. indica leaf dust were found ineffective to cause adult mortality (20.33 and 19.67) and adult emergence (1549 and 2292) in chickpea. Malathion, initially was found somewhat effective in adult mortality (21.67) and adult emergence (30.33). However, it was less effective from F2 generation resulting maximum adult emergence (2127). While comparing two storage structures, jute bag with plastic lining was better in terms of maintaining lower moisture (14.64%), higher germination (65.14%) and lesser grain damage (39.95%). Thus, the jute bag with plastic lining was found as a better storage structure and botanical materials such as A. calamus rhizome dust, Sesamum oil and C. camphora balls have been found as effective safe alternatives for the management of C. chinensis L. in the storage of chickpea. The Journal of Agriculture and Environment Vol:12, Jun.2011, Page 81-90 DOI: http://dx.doi.org/10.3126/aej.v12i0.7567